OrbiTox: a visualization platform for NAMs and read-across exploration of multi-domain data - Ross, Austin; Gombar, Vijay; Sedykh, Alexander; Green, Adrian J.; Borrel, Alexandre; Kidd, Brian; Phillips, Jason; Shah, Mihir; Phadke, Dhiral; Mav, Deepak; Balik-Meisner, Michelle; Howard, Brian; et al. (Frontiers in Pharmacology, 2025)
The development of new approach methodologies (NAMs) for next-generation risk assessment (NGRA) requires the integration of diverse data streams. A comprehensive understanding of a chemical’s potential hazard involves combining multiple mechanistic data, usually from in vitro and in silico studies, to build a coherent weight-of-evidence case. Currently, the lack of tools to effectively aggregate and navigate disparate datasets makes regulatory evaluation a challenging process. OrbiTox addresses this need by consolidating millions of data points from multiple domains, i.e., chemical properties, genes, pathways, and bioactivities, into an intuitive and interactive 3D visualization platform. To support comprehensive chemical assessments, OrbiTox incorporates hundreds of quantitative structure–activity relationship (QSAR) models for robust gap-filling of key endpoints. It also facilitates read-across by enabling the retrieval of data-rich chemical analogs with similar structures and metabolic profiles. By unifying experimental data and predictive models within a user-friendly interface, OrbiTox facilitates data-driven chemical safety assessments.